Analysis of Affective Aspects in Samarinda Vocational School Students in Physics Learning During a Pandemic - Siti Norhasanah; Riskan Qadar; Zeni Haryanto (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the affective assessment of students in learning physics during the pandemic. This affective assessment is carried out by means of self assessment, which is an affective assessment carried out by students towards themselves as seen from the attitudes of students during physics learning. The type of research used is descriptive quantitative research. The data collection instrument used a questionnaire in the form of 20 questions with a Guttman scale distributed via google form. The population in the study were students from one of the Samarinda vocational high school with a total sample of 68 students in class X Heavy Equipment Engineeringand 2. The results showed that the affective assessment of students was included in the good category, the indicator received the percentage obtained was 87.50%, responding 82.72 %, value 76.47%, value conceptualization 77.20%, and value characterization 77.20%.